Penguatan Moderasi Beragama melalui Nilai-nilai Al-Qur’an dalam Tradisi Wungon di Pemalang - Safitri, Hani Hasnah; Khumaedy, Agus; Ta'rifin, Ahmad; Albab, Ulul (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Indonesia has the advantage of being a peaceful and prosperous country with diverse religions and cultural traditions. This research aims to examine tolerance and harmony in the